2022
DOI: 10.1167/iovs.63.5.20
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Acquired Color Deficiency and PET Imaging of Neurodegeneration in Mild Cognitive Impairment and Alzheimer Disease

Abstract: Purpose To evaluate color vision changes and retinal processing of chromatic and luminance pathways in subjects with Alzheimer disease (AD) and mild cognitive impairment (MCI) compared with a matched control group and whether such changes are associated with impaired brain glucose metabolism and β-amyloid deposition in the brain. Methods We evaluated 13 patients with AD (72.4 ± 7.7 years), 23 patients with MCI (72.5 ± 5.5 years), and 18 controls of comparable age ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
(90 reference statements)
2
1
1
Order By: Relevance
“…With respect to the deutan axis, we found statistically significant differences when we compared between the control group and both mild and moderate AD and when we compared between the FH+ and moderate AD groups. Similar than Vidal et al (2022), we also found no significant differences in the number of errors between the control and MCI groups.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…With respect to the deutan axis, we found statistically significant differences when we compared between the control group and both mild and moderate AD and when we compared between the FH+ and moderate AD groups. Similar than Vidal et al (2022), we also found no significant differences in the number of errors between the control and MCI groups.…”
Section: Discussionsupporting
confidence: 74%
“…Also, the moderate AD group showed a significant increase in the total number errors related to control group. This diffuse involvement has been observed by different authors (Pache et al, 2003;Salamone et al, 2009;Polo et al, 2017;Salobrar-García et al, 2019) and recently Vidal et al had found that individuals with AD and those with MCI display an acquired color vision deficiency, both in protan and tritan axism that is likely associated with compromised brain metabolism (Vidal et al, 2022).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Various factors play a role in the development of acquired CVD, which cause problems in the reception and transmission of color signals to the brain by disrupting the visual system [3] . Among these factors are ocular diseases including cataracts [4] , refractive errors [5] , agerelated macular degeneration (AMD) [6] , glaucoma [7] , and retinal diseases [8] , neurological factors [9] , metabolic factors [10] , chronic diseases such as diabetes mellitus [11] , viral diseases such as COVID-19 [12] , drugs and toxins [13] , occupational [14] , and aging [15] .…”
Section: Introductionmentioning
confidence: 99%